Early Edema Within the Ischemic Core Is Time-Dependent and Associated With Functional Outcomes of Acute Ischemic Stroke Patients - Han, Qing; Yang, Jianhong; Gao, Xiang; Li, Jichuan; Wu, Yuefei; Xu, Yao; Shang, Qing; Parsons, Mark W.; Lin, Longting (Frontiers in Neurology, 2022)
Objective: To investigate the difference in early edema, quantified by net water uptake (NWU) based on computed tomography (CT), between ischemic core and penumbra; to explore predictors of NWU and test its predictive power for clinical outcome. Methods: Retrospective analysis of patients admitted to Ningbo First Hospital with anterior circulation stroke and multi-modal CT. In 154 included patients, NWU of the ischemic core and penumbra were calculated and compared by Mann–Whitney U test. Correlations between NWU and variables including age, infarct time (time from symptom onset to imaging), volume of ischemic core, collateral status and National Institutes of Health Stroke Scale (NIHSS) scores were investigated by Spearman’s correlation analyses. Clinical outcome was defined by modified Rankin Scale (mRS) at 90 days. Logistic regression and receiver operating characteristic (ROC) analyses were performed to test the predictive value of NWU. Summary statistics are presented as median [interquartile range] or mean (standard deviation); estimates as estimate (95% confidence interval). Results: The NWU within ischemic core (6.1%, [2.9%-9.2%]) was significantly higher than that of penumbra (1.8% [-0.8%-4.0%]). The only significant predictor of NWU within ischemic core was infarct time (p=0.004). The NWU within ischemic core (odds ratio=1.23 [1.10-1.39]), volume of ischemic core (1.04, [1.02-1.06]), age (1.09, [1.01- 1.17]) and admission NHISS score (1.05, [1.01-1.09]) were associated with outcome of patients adjusted for sex and treatment. The predictive power for outcome of the model was significantly higher when NWU was included (area under the curve 0.875 versus 0.813, p<0.05 by Delong test). Conclusions: Early edema quantified by NWU is relatively limited in the ischemic core and developing in a time-dependent manner. NWU estimates within the ischemic core may help to predict clinical outcomes of acute ischemic stroke patients.